Compressible Waste Bin System for Public Environment : Design with a User-Centred Approach - Nilsson, Joel (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
We consume more and more which also have led to an increase in the waste we most handle. In public environment, common solution have been to increase the size of the waste bin, but that’s not always an option. To big and it may interfere with the environment it placed in. Another approach is to compress the disposed waste and so increase the waste bins capacity without increasing the volume of the wastebin itself. BigBelly is one product which have embraced this apprach. It is a solar driven compressing waste bin commonly seen in big cities around the world. The problem is that some miner municipalities and private companies still are in need of a solution but don’t have the resources to obtain BigBellys or other similar solutions. One way to approach this market is to develop a waste bin without the electric usually expensive components and develop a less expensive compressible waste bin that’s still an effective choice. To understand the needs, both of those who dispose of waste publicly but also those who manage the waste bins, have interviews, observations, questionaries and focus groups been used to gather valuable data. This data have then been remade in terms of user needs and ranked according to importance by the users themselves and the project manager. Some highly ranked needs are: the waste bin is steady and robust, the waste bin can only be opened by those who handle/empty the waste bins, a manual compression can be performed by those who throw the waste, and a manual compression can be performed without any major effort. By the method Design by analogies and a workshop held at Luleå University of Technology was ideas created. The three concepts with the highest potential were selected via Pugh’s selection matrix and tested according to efficiency and effectivity. The concept with the highest result was developed in Simens NX a CAD-program and then used as a template for the construction of a functional prototype. By testing and analyzing the prototype a product specification could be created. The ...